Development of Alphabet Word Card Media on Thematic Learning for Elementary School Students - Faralia, Dina; Basri, Amin (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to develop learning media for alphabet word cards in thematic learning theme 3, "Objects Around Me," for grade 2 students at SD Muhammadiyah 01 Medan. This research uses research and development with the EDDIE model, which is limited only to measuring the extent of its validity by using two expert validators to validate learning instruments in the form of content and learning media through three stages, namely analysis, design, and development. The data collection technique uses a validation sheet. The data analysis technique uses the product-moment correlation test. Based on the results of the alphabet word media validation test, it can be concluded that the validation of the alphabet word card media by media experts obtained a score of 77.999% in the appropriate category. The researcher's validation of the alphabet word card media obtained an average score of 90.476% in the feasible category. Validation of the learning implementation plan obtained an average score of 89.35% in the very effective category. Alphabet word card media is said to be effective. The media is declared valid or very suitable for teaching material in Learning. This can be the basis for teacher information in using alphabet word media in thematic Learning with the theme "objects around me" in selecting learning media in the future.